2016
DOI: 10.1016/j.cmi.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of community-associated methicillin-resistant Staphylococcus aureus  strains in the neonatal intensive care unit: an infection prevention and patient safety challenge

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) infections cause significant morbidity and mortality in neonatal intensive care units (NICUs). We characterized the clinical and molecular epidemiology of MRSA strains colonizing NICU patients. Nasal MRSA isolates (n=250, from 96 NICU patients) recovered through active surveillance from 2009-2014 were characterized with Staphylococcal cassette chromosome mec (SCCmec) typing and detection of mupA (marker of high-level mupirocin resistance) and qacA/B (marker as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…Previous studies of children have shown an association between antiseptic tolerance genes in S. aureus and the presence of central venous lines (CVLs), as well as a higher rate of invasive infection (18). Many previous pediatric studies, however, have been biased by including high-risk populations, such as neonates/infants and oncology and cardiac surgery patients (12,18,20,21).…”
mentioning
confidence: 99%
“…Previous studies of children have shown an association between antiseptic tolerance genes in S. aureus and the presence of central venous lines (CVLs), as well as a higher rate of invasive infection (18). Many previous pediatric studies, however, have been biased by including high-risk populations, such as neonates/infants and oncology and cardiac surgery patients (12,18,20,21).…”
mentioning
confidence: 99%
“…Approximately 1 out of 5 neonates colonized with MRSA may develop an infection [5, 6, 18, 19], corresponding to a relative risk of 24.2 (95% CI 8.9–66.0) compared to noncolonized neonates [16]. The median time between MRSA colonization and the onset of infection may range from 4 to 9 days [18, 20].…”
Section: Neonatal Mrsa Colonization and Infectionsmentioning
confidence: 99%
“…The incidence of MRSA infections in neonates with a BW ≤1,000 g has been reported to be 53.4 per 10,000 infants, compared to 23.2, 7.9, and 5.0 per 10,000 infants in the BW categories of 1,001–1,500, 1,501–2,500, and > 2,500 g, respectively [2]. Other risk factors for MRSA infections include prolonged hospitalization, overcrowding and understaffing in neonatal wards, long-term use of respiratory support, intravascular catheters, antibiotics, and total parenteral nutrition, as well as surgical procedures [6, 18, 19]. The clinical manifestation of MRSA infections may range from mild focal infections, such as conjunctivitis and skin and soft tissue infections, to more severe forms like toxic shock syndrome [24] and even invasive infections such as sepsis, necrotizing pneumonia, meningitis, endocarditis, osteomyelitis, liver abscesses, and urinary tract infections [2, 18, 23, 25-27].…”
Section: Neonatal Mrsa Colonization and Infectionsmentioning
confidence: 99%
See 2 more Smart Citations